Classical Guidance Model with Problem-Based Learning Technique to Improve Students' Empathy in Inclusive State Junior High School in Yogyakarta - Sabila, Novira Silmi; Astuti, Budi; Arifudin, Moch (Department of Special Education, 2025)
Inclusive schools have an important role in creating a friendly educational environment for all students, including those with special needs. One important aspect in creating an inclusive school is increasing empathy of regular students towards their friends with special needs. This study aims to develop and test the feasibility and practicality of the classical guidance model with problem-based learning techniques to increase regular students' empathy towards children with special needs in guidance and counseling services at 10 Inclusive State Junior High Schools in Yogyakarta. This research is research and development with the Borg & Gall model with 7 stages: (1) initial research and information gathering; (2) planning and design; (3) initial product development; (4) initial field testing; (5) initial product revision; (6) main field testing; (7) operational product revision. The research subjects involved one material expert, one model expert, one instrument expert, 10 Guidance and Counseling teachers, and 100 students. Data collection techniques included interviews, observations, questionnaires, and empathy scales. The results of this study indicate that: (1) the classical guidance model produces very feasible products by model experts with a score of 92% and material experts with a score of 93%; (2) the classical guidance model produces practical products by Guidance and Counseling teachers with a score of 88%. The product scores that have been given by experts can be applied in schools and influence regular students to increase empathy. This research still needs further development by developing science, can be applied in various other schools and further strengthen the implementation of inclusive education in Indonesia.